2014
DOI: 10.1186/2046-0481-67-13
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterisation of bovine rotavirus in Ireland from 2006–2008

Abstract: BackgroundWorldwide, Group A bovine rotavirus (RVA boRV) is one of the main causes of neonatal calf diarrhoea. Currently, limited epidemiological and sequence data exists on the RVA disease in bovines in Southern Ireland only. The aim of the study was to generate epidemiological and sequence data of RVA boRV distributed over a wide geographical area in Ireland.Findings272 stool samples were obtained from symptomatic calves and analysed to identify the prevalent G and P genotypes. Viral type combinations includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…Bootstrap values are shown at branch nodes. The Korean isolates identified in this study are indicated by a circle symbol and in bold Badaracco et al 2013;Collins et al 2014;Fukai et al 2004;Park et al 2011). All our isolates detected in this study were assigned to G6P [5].…”
Section: Discussionmentioning
confidence: 99%
“…Bootstrap values are shown at branch nodes. The Korean isolates identified in this study are indicated by a circle symbol and in bold Badaracco et al 2013;Collins et al 2014;Fukai et al 2004;Park et al 2011). All our isolates detected in this study were assigned to G6P [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, G6P [11] has been incriminated as a cause of a diarrhea outbreak in a beef herd (Medeiros et al 2014a), although there are also reports of its occurrence as the most common genotypic combination in some states of country (Silva et al 2012). In Ireland, G6P[11] is reported as a low prevalence genotypic combination found especially in dairy herds (Collins et al 2014), while in Turkey, Alkan et al (2010) reported a high prevalence of this genotype in either unvaccinated herds and in herds immunized against G6P [1].…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto and colleagues (64) considered that their isolates represented reassortment events between bovine-like human rotaviruses and human/feline AU-1-like rotaviruses. G6 is a common genotype in cattle/buffalo (67)(68)(69)(70), sheep (71)(72)(73), and goats (74,75) and has been identified sporadically or at a low prevalence in rabbits (76) and pigs (77,78). It is uncommon in people, and although a zoonotic origin is postulated (64,(79)(80)(81)(82)(83), it has not yet been convincingly proven whether such zoonotic strains spread among people.…”
Section: Discussionmentioning
confidence: 99%